Wastewater treatment and reuse costs: a Middle-East case - Abulbasher M. Shahalam; Shahjabin Alam; Al-Rashidi Hader (2005)
Shortage of water has led many regions of the world to think seriously about reuse of wastewater effluent for non-domestic uses. The cost of water production for reuse is of great interest. The paper presents comparative figures of costs for sewage collection, sewer system, house connection, various levels of treatment and centralized management of wastewater storage and distribution. The State of Kuwait in the Middle-Eastern region is used as the case.